Translational potential of allosteric modulators targeting the cannabinoid CB1 receptor - Lu Dai; Immadi Sri Sujana; Wu Zhixing; Kendall Debra A. (Acta Pharmacologica Sinica, 2019)
The cannabinoid type-1 (CB1) receptor, a G-protein-coupled receptor, is an attractive target for drug discovery due to its involvement in many physiological processes. Historically, drug discovery efforts targeting the CB1 receptor have focused on the development of orthosteric ligands that interact with the active site to which endogenous cannabinoids bind. Research performed over the last several decades has revealed substantial difﬁculties in translating CB1 orthosteric ligands into druggable candidates. The difﬁculty is mainly due to the adverse effects associated with orthosteric CB1 ligands. Recent discoveries of allosteric CB1 modulators provide tremendous opportunities to develop CB1 ligands with novel mechanisms of action; these ligands may potentially improve the pharmacological effects and enhance drug safety in treating the disorders by regulating the functions of the CB1 receptor. In this paper, we review and summarize the complex pharmacological proﬁles of each class of CB1 allosteric modulators, the development of new classes of CB1 allosteric modulators and the results from in vivo assessments of their therapeutic value.